Study Protocol for a Randomised Controlled Trial on Pulmonary Metastasectomy vs. Standard of Care in Colorectal Cancer Patients With ≥ 3 Lung Metastases (PUCC-Trial) - Schmid, Severin; Becker, Heiko; Fritsch, Ralph; Bausch, Johannes; Hunter, Natalie; Jenkner, Carolin; Hassan, Mohamed; Passlick, Bernward (Frontiers in Oncology, 2022)
This is a multicentre prospective randomised-controlled trial for patients with 3 or more resectable pulmonary metastases from colorectal carcinoma. The study investigates the effects of pulmonary metastasectomy in addition to standard medical treatment in comparison to standard medical treatment plus possible local ablative measures such as SBRT. This trial is intended to demonstrate an overall survival difference in the group undergoing pulmonary metastasectomy. Further secondary and exploratory endpoints include quality of life (EORTC QLQ-C30, QLQ-CR29 and QLQ-LC29 questionnaires), progression-free survival and impact of mutational status. Due to the heterogeneity and complexity of the disease and treatment trajectories in metastasised colorectal cancer, well powered trials have been very challenging to design and execute. The goal of this study is to create a setting which allows treatment as close to the real life conditions as possible but under well standardised conditions. Based on previous trials, in which patient recruitment in the given setting hindered successful study completion, we decided to (1) restrict inclusion to patients with 3 or more metastases (since in case of lesser, surgery will probably be the preferred option) and (2) allow for real world standard of care (SOC) treatment options before and after randomisation including watchful waiting (as opposed to a predefined treatment protocol) and (3) possibility that patient can receive SOC externally (to reduce patient burden). Moreover, we chose to stipulate 12 weeks of systemic treatment prior to possible resection to further standardize treatment response and disease course over a certain period of time. Hence, included patients will be in the disease state of oligopersistence rather than primary oligometastatic. The trial was registered in the German for Clinical Trials (DRKS-No.: DRKS00024727).